A review of ethics in developing country in perspective of dental research - Khan, Md Haider Ali; Lasker, Shamima Parvin (Bangladesh Journal of Bioethics, 2014)
The objectives of this review were to examine the ethical issues in research in developing country and perspective of dental research. In this review, we performed the systematic literature search, screening process through the web in existing published and unpublished articles and reports that related to our topics between1990 to 2013. In the past few decades, the research and discoveries in the discipline of dentistry have increased dramatically. Recently many dental Institutes in developing country is constantly looking for opportunities to borrow, enhance, and integrate knowledge from biomedical and technological research by using modern technology. The retrieved information in this review reflect that to make any research involving human subjects ethically acceptable, a number of key features have to be considered by the researchers. Those who conduct oral health research are compelled by regulations and convention to follow established ethical standards to protect human rights. Bioethics and in ethical review of research in developing countries reveals many major gaps and have seen that there are indeed many ethical issues to be considered to clinical trials taking place in developing countries. Professional societies have a major influence in shaping the moral tone and ethical climate for research through the adoption of standards, the development of educational programs designed to reinforce those standards. Research ethics committees or institutional ethical review committees is to ensure that studies involving human research participants are designed to conform the relevant ethical standards and that the rights and welfare of participants are protected. Research ethics committees should not function under the influence of others and should ensures the favorable balance of potential benefits and risks. In developing country it is necessary to strengthen local capacity and manpower by developing innovative training models for ethics that are cost-effective and sustainable. The actions required to move ahead in this field include strengthening bioethics capacity, linking health research to community needs in a transparent and participatory process and increasing communication between scientists and ethicists in industrialized and developing countries. DOI: http://dx.doi.org/10.3329/bioethics.v5i1.18443 Bangladesh Journal of Bioethics 2014 Vol.5(1): 11-19